Global Stability for Fractional Diffusion Equations in Biological Systems. (5th August 2020) - Hattaf, Khalid; Yousfi, Noura
Abstract : This paper proposes a new method of construction of Lyapunov functionals for the dynamical systems described by fractional differential equations and fractional partial differential equations. The proposed method is rigorously presented. Furthermore, the method is applied to establish the global stability of some fractional biological models with and without diffusion.